Cybersecurity breaches and cash holdings: Spillover effect. Issue 2 (15th May 2019) - Garg, Priya
Abstract: This paper shows that firms significantly increase cash holdings after they have experienced a cybersecurity attack, and this behavior persists for years. A cyberattack increases cash holdings from a base level of 23% of assets to 26.87%. Similar firms, defined by industry and geographical proximity also increase their cash holdings. Suppliers of attacked firms are also affected. Overall, the results of this study indicate that the detrimental effects of a cybersecurity breach are not isolated to the attacked firms, and peer firms are quick to follow in taking precaution.